High-throughput sequencing technology reveals that continuous cropping of American ginseng results in changes in the microbial community in arable soil - Linlin Dong; Jiang Xu; Lianjuan Zhang; Juan Yang; Baosheng Liao; Xiwen Li; Shilin Chen (BMC, 2017)
Abstract Background American ginseng (Panax quinquefolius L.) is renowned worldwide for its eutherapeutic effects. The replantation of American ginseng usually fails due to problems associated with continuous cropping. An imbalance in the microbial community is thought to be responsible for this, but the overall changes in microbial communities under a continuous cropping system are unclear. Methods This study used quantitative polymerase chain reaction combined with high-throughput sequencing methods to confirm changes in a microbial community under continuous cropping of American ginseng. Results Copy numbers of bacteria and fungi significantly declined by 47.7 and 45.5%, respectively, upon American ginseng cropping over 3 years. A total of 66,391 classified sequences were obtained from high-throughput sequencing analyses of 16S and 18S rRNA in six soil samples. A decline in bacterial diversity and an increase in fungal diversity were observed in the continuous cropping soils of American ginseng compared to those of traditional crops. Compared with soils used for traditional crops, the relative abundance of bacterial and fungal groups changed in soils subjected to continuous cropping with American ginseng. Conclusions Our results revealed that the diversity and composition of soil bacterial and fungal communities changed in the continuous cropping of American ginseng compared to those of traditional crops. Those data provided comprehensive insight into microbial communities at the agro-ecosystem scale and contributed to the understanding of micro-ecological environments in the rhizosphere of medicinal plants.